TINJAUAN ASPEK KELAYAKAN ELEMEN PEMBENTUK RUANG KOMUNAL DI TAMAN MONUMEN 45 KOTA PEKALONGAN - Moch Fathoni Setiawan; Andi Purnomo (Jurnal Teknik Sipil dan Perencanaan)
Taman Monumen 45 is one of the city park in Pekalongan City, in which there are statues of the heroes as monument to commemorate the services of the heroes. In this park there are also garden element in shape of hard elements and soft elements. Some hard elements are sitting group, pedestrian area, sports area, and the statue of the heroes (sculpture). The hard elements are referred to support the communal activity for the citizens of Pekalongan. They are functioned as for gathering and chatting, lounging, skateboarding and BMX styling. This study aims to assess the feasibility aspects in Taman Monumen 45 in Pekalongan City. From the research, it was revealed that there are some elements of the park that do not meet the eligibility aspect as constituting elements of communal space. It can be seen from the condition of these elements, either hard material or soft material that is still less maintained and is not in accordance with its function.